A Survey Study on Freetime Behaviour of Undergraduate Students in Mechanical Engineering Program - Wasananon, Supachai; Sirisomboon, Kasama; Sangsawang, Thibodin; Wasananon, Dolruedee (Food Agricultural Sciences and Technology, 2019)
This research purposed to study on freetime behaviours of undergraduate students in Mechanical Engineering program at Silpakorn University during their freetime and the correlation between their behaviours and their learning achievements via using the mixed methods research. The sample were 347 students in semester year 2/2016. The research instruments included questionnaire and structured interview. The data were statistically analyzed by using frequency, percentage, mean, S.D. and One-way ANOVA. The research findings were as follows: The students spent the average of 75.54 hours per week or 35.26 hours per week (46.68%) on resting, 21.42 hours per week (28.36%) on their study, 16.79 hours per week (22.23%) on others, and 2.07 hours per week (2.74%) on doing exercises, respectively. The correlation between behaviours and learning achievements of students studying the Bachelor of Engineering Program in Mechanical Engineering at Silpakorn University shows that spending time on studying, resting, doing exercises, and other activities, and the learning achievements of the three groups were different and statistically significant at the 0.05 level.